Evaluating the Potential of Brown Sugar Product as An Effort to Increase the Economic Welfare of Coconut Farmers in Sidorejo Village, Kapenewon Lendah, Kabupaten Kulon Progo - Fani Pramuditya; Leo Indra Wardhana; Saiqa Ilham Akbar; Elton Buyung Satrianto (Jurnal Pengabdian dan Pengembangan Masyarakat, 2022)
This study aims to give innovation and value added to the brown sugar produced by the community in Sidorejo Village. The purpose is to provide a better income for the coconut farmer  as well as to optimize the roles of BUMDES Binangun Dadi Maju as an economic catalyst. This project was conducted in Desa Sidorejo, Kapenemon Lendah, Kabupaten Kulon Progo, Daerah Istimewa Yogyakarta. There are three stages applied in this program i.e.: preparation, application and evaluation. Recommendations and guidance were given to the farmer and BUMDES to develop the brown sugar product and to produce the liquid brown sugar product. The new product development is still under evaluation for the commercial purpose.